Analisis Situasi Masalah Kesehatan Penyakit Menular di Provinsi Kalimantan Barat - Luqman Luqman; Mondastri Korib Sudaryo; Antonius Suprayogi (Jurnal Epidemiologi Kesehatan Komunitas, 2022)
Background: Health problems in West Kalimantan are dominated by infectious diseases based on health data showing that the list of the top 10 diseases is dominated by infectious diseases, the CFR rate is still quite high and outbreaks routinely occur due to infectious diseases. The purpose of the situation analysis is to determine priorities for infectious disease problems in West Kalimantan in 2019.Methods: This research was conducted from December 2020 to February 2021 in West Kalimantan Province. The research method used is an assessment method whose results will be presented descriptively with quantitative and qualitative approaches. Determining the priority of the problem using the PAHO-Adapted Hanlon method with assessment criteria based on the size of the problem, seriousness of the problem, intervention effectiveness, inequity and institutional factors by means of interviews with related parties within the West Kalimantan Provincial Health Office.Result: The results of the analysis of infectious disease problems in West Kalimantan Province show that the top 10 diseases are still dominated by infectious diseases such as diarrhea, TB and DHF. The CFR figure which is still quite high is contributed by TB, HIV/AIDS, diphtheria and DHF. In this study, TB was selected as a priority health problem because it obtained the highest PAHO score of 25.16. TB is still a major problem because case finding has not reached the national target of 80%, there is still transmission in the community and cases of TB in children are still quite high.Conclusion: Tuberculosis is a priority infectious disease problem in West Kalimantan. TB is the first priority problem in this study because case finding is not optimal, there is transmission in the community and there are still cases of TB in children. It is hoped that with monitoring and evaluation of training for cadres and health workers, screening of TB patients can be more massive and sensitive for providing complete TB treatment.